A Review of assessment in adaptive reuse of heritage buildings in Malaysia / Hasni Suryani Mat Hasan, Lilawati Ab Wahab and Dzulkarnaen Ismail - Mat Hasan, Hasni Suryani; Ab Wahab, Lilawati; Ismail, Dzulkarnaen (2018)
Heritage buildings is one of the urban identities for the city and should be well-preserved not only because of the value and story, it also because of existing building stock. Reusing existing building stock can combat the environmental load significantly by reducing the material, transport, energy consumption and pollution in construction of new building. In recent years, adaptive reuse of heritage buildings is popping out so fast, compared to previous year wherebyheritage building mainly suffers from dilapidated and poor building conditions. Adaptive reuse is converting the original function of existing buildings which services and technology are outdated to a new building purpose for a new need to meet the current development. However, theeagerness of owner and local authority in applying the adaptive reuse approach in heritage buildings, which this approach has been recently criticised for jeopardizing the authenticity of the heritage buildings. Hence, the aim of this study isto review previous studies on assessment method implement in adaptive reuse project based on the authenticity principle in conservation for heritage building. It is believed that this studycan help increasethe percentage of authenticity by creating an awareness between stakeholders. This study involved reviewing relevant research to embrace all information pertaining toassessment in adaptive reusefor heritage building.It is hoped that the outcome of this study will help organisation or individual who are interested in adaptive reuse for future references.